CONSUMER BEHAVIOR-BASED DIGITALIZATION FOR COMPETITIVENESS OF THE CULINARY SME INDUSTRY IN MANADO - Harley Mangindaan; Priskila Walangitan; Vallery Mewoh; Verginia Ombeng (SOSIOEDUKASI, 2025)
One of the national strategic goals is digital transformation, and 30 million MSMEs are expected to become digital by 2024. Nevertheless, Manado culinary MSMEs, especially those in the Flamboyan Street Food District, continue to experience a digital divide because consumer behaviour is becoming increasingly reliant on social media content, online reviews, and electronic money transfer systems. The proposed study will help develop a consumer-behaviour-based digital strategy model to enhance the competitiveness and sustainability of culinary MSMEs. An explanatory mixed-methods research design was used to gather quantitative data (100 digital consumers) using PLS-SEM and qualitative data (in-depth interviews, FGDs, and direct observations of MSME actors). The results show that customer engagement strongly mediates the influence of digital strategy on competitiveness and that competitiveness is a strong personal contributor to business sustainability. The qualitative findings indicate that digital literacy, regular online promotion, and enabling infrastructure are essential to the adoption of digital technology. In general, this study has found that consumer-focused digital approaches can enhance the competitiveness and sustainability of MSMEs in the culinary industry in Manado. Practical recommendations include the establishment of digital marketing strengths, multi-stakeholder cooperation, and the adoption of context-related technologies in line with the local culture and groups.